SNACK BAR FORMULATION WITH BLACK GLUTINOUS RICE FLOUR AND RICE BRAN: REDUCING SUGARS, PROXIMATE COMPOSITION, AND SENSORY ACCEPTANCE - Ilya Assyahra; Muhammad Irfan Febriansyah; Hanif Muchadatul Ayunda; Wardah Iskandar (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
This study developed gluten-free, low-sugar snack bars by valorizing underutilized black rice flour (BR) and rice bran flour (RB) to address health concerns in conventional formulations. Employing a factorial completely randomized design (BR: 10-30%, RB: 10-20%), we evaluated six formulations through proximate analysis, reducing sugar assays, and organoleptic testing (n=75 untrained panelists). The 10% BR + 10% RB formulation emerged as optimal, demonstrating superior sensory acceptance across all parameters (overall hedonic score: 5.53±1.09) and favorable nutritional profile: 5.72% moisture, 25.54% fat, 9.61% protein, and 57.3% carbohydrates. Contrastingly, 20% BR + 10% RB showed the highest reducing sugar content (8.00±0.33 g/mL) but suboptimal sensory appeal. Nutritional variability was formulation-dependent: increased BR substitution elevated moisture (p<0.05) and ash content (p<0.01) due to amylose-mediated water absorption and mineral enrichment, while higher RB proportions reduced carbohydrate content (p<0.01) through nutrient displacement. Although the optimal formulation achieves sensory-nutritional balance, compositional refinement remains necessary for full compliance with Indonesian National Standards (SNI). This research establishes a sustainable framework for transforming agricultural byproducts into functional foods..